Modelling stick-slip dynamics in frictional fluids - Bjornar Sandnes (Geophysical Research Abstracts 15, EGU2013-14040, 2013)
Dissipative interactions between grains often lead to instabilities and pattern formation in flows involving granularmaterials. This is especially so in wet granular flows, where viscous and capillary forces add to the complexdynamics. In a recent study we found an extraordinary diversity in the flow behaviour of wet granular materialdisplaced by air in a Hele-Shaw cell [1]. By varying the air injection rate, system compressibility, and granularmaterial filling fraction, several distinct flow morphologies were observed. The study maps these out in phasediagrams.Here we present a numerical model that focuses on one of the observed pattern transitions; from frictionalfingering to stick-slip bubbles. By incorporating surface tension, pressure and frictional forces, we trace thedisplacement of the interface using a dynamical version of a quasi-static algorithm developed previously [2]. Themodel reproduces the growth and evolution of the flow dynamics, resulting in patterns that closely resemble thoseobserved in the experiments. The numerical scheme offers a method to study the transition between the patternformation modes in detail, complementary to the experimental results.